Temperate macroalgae impacts tropical fish recruitment at forefronts of range expansion - Beck, H.J.; Feary, David A.; Nakamura, Y.; Booth, David J. (Springer Verlag, 2017)
Warming waters and changing ocean currents are increasing the supply of tropical fish larvae to temperature regions where they are exposed to novel habitats, namely temperate macroalgae and barren reefs. Here, we use underwater surveys on the temperate reefs of southeastern (SE) Australia and western Japan (~33.5°N and S, respectively) to investigate how temperate macroalgal and non-macroalgal habitats influence recruitment success of a range of tropical fishes. We show that temperate macroalgae strongly affected recruitment of many tropical fish species in both regions and across three recruitment seasons in SE Australia. Densities and richness of recruiting tropical fishes, primarily planktivores and herbivores, were over seven times greater in non macroalgal than macroalgal reef habitat. Species and trophic diversity (K-dominance) were also greater in non macroalgal habitat. Temperate macroalgal cover was a stronger predictor of tropical fish assemblages than temperate fish assemblages, reef rugosities or wave exposure. Tropical fish richness, diversity and density were greater on barren reef than on reef dominated by turfing algae. One common species, the neon damselfish (Pomacentrus coelestis), chose nonmacroalgal habitat over temperate macroalgae for settlement in an aquarium experiment. This study highlights that temperate macroalgae may partly account for spatial variation in recruitment success of many tropical fishes into higher latitudes. Hence, habitat composition of temperate reefs may need to be considered to accurately predict the geographic responses of many tropical fishes to climate change.